2017
DOI: 10.1002/pros.23360
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of LHRH and development of LHRH analogs for prostate cancer treatment

Abstract: The discovery, isolation, elucidation of structure, synthesis, and initial testing of the neuropeptide hypothalamic luteinizing hormone-releasing hormone (LHRH), which regulates reproduction, is briefly described. The design, synthesis, and experimental and clinical testing of agonistic analogs of LHRH is extensively reviewed focusing on the development of new methods for the treatment of prostate cancer. Subsequent development of antagonistic analogs of LHRH is then faithfully recounted with special emphasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 160 publications
(281 reference statements)
1
34
0
1
Order By: Relevance
“…This suggests that the down-regulation of GHRH-Rs leads to an inhibition of tumor growth. This situation appears to be similar and comparable to the well-known phenomenon of the down-regulation of pituitary receptors for luteinizing hormone-releasing hormone (LHRH) by LHRH agonists (44)(45)(46). It is well established that an acute administration of superactive agonists of LHRH induces a marked release of luteinizing hormone (LH) and follicle-stimulating hormone (FSH).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This suggests that the down-regulation of GHRH-Rs leads to an inhibition of tumor growth. This situation appears to be similar and comparable to the well-known phenomenon of the down-regulation of pituitary receptors for luteinizing hormone-releasing hormone (LHRH) by LHRH agonists (44)(45)(46). It is well established that an acute administration of superactive agonists of LHRH induces a marked release of luteinizing hormone (LH) and follicle-stimulating hormone (FSH).…”
Section: Discussionsupporting
confidence: 68%
“…However, chronic administration of LHRH or its agonists leads to a suppression of circulating levels of FSH, LH, and sex steroids. This effect is produced by the desensitization of gonadotroph cells and the downregulation of pituitary receptors for LHRH and is utilized for the inhibition of sex hormone-dependent cancers (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, two types of GnRH-R are known to exist in primates, with only a functional type I GnRH-R existing in human tissues (4). Studies have demonstrated that GnRH-R is overexpressed in many human tumors (e.g., breast, ovarian, endometrial, and prostate cancers), whereas it is not expressed or expressed at very low levels in adjacent normal tissues (5)(6)(7). Accumulating evidence has demonstrated that more than 80% of ovarian and endometrial cancers, as well as more than 50% of breast cancers, have high levels of GnRH-R expression (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we note that an luteinizing‐hormone releasing hormone (LHRH) antagonist (Cetrorelix), which brought down serum testosterone to castrate levels in a rat model of BPH, reduced prostate size and blunted the expression of pro‐inflammatory cytokines and growth factors . Accordingly, the suitability of LHRH antagonism in BPH therapy is currently being explored . We speculate that the androgen/androgen receptor (AR)‐regulated signaling network may be impacted by the SASP secretome, and genetic or pharmacologic targeting of downstream effectors of the AR pathway may further inform new avenues for controlling BPH pathogenesis.…”
Section: Discussionmentioning
confidence: 99%